Highly efficient removal of toxic Pb2+ from wastewater by an alginate–chitosan hybrid adsorbent. Issue 9 (2nd April 2018) - Wang, Zhuqing; Jin, Pengxiang; Wang, Min; Wu, Genhua; Sun, Jiayin; Zhang, Yujie; Dong, Chen; Wu, Aiguo
Abstract: BACKGROUND: In this study, a low‐cost and environment‐friendly alginate–chitosan hybrid adsorbent (depicted as Alg‐Chi) was developed for the removal of Pb 2+ from water. RESULTS: Experimental results showed that the Alg‐Chi exhibits high selectivity and affinity for Pb 2+ . The selectivity coefficients of the Alg‐Chi for Pb 2+ /Cr 3+, Pb 2+ /Co 2+ Pb 2+ /Cd 2+, Pb 2+ /Zn 2+, and Pb 2+ /Cu 2+ are all >5. It can uptake 96.8% of Pb 2+ from Pb 2+ ‐containing solutions (1.5 mmol L −1 ), and the maximum adsorption capacity for Pb 2+ reaches 468.5 mg g −1, which is higher than that of most reported adsorbents for Pb 2+ . Moreover, the Alg‐Chi can also be regenerated via simple acid elution and used repeatedly without loss in adsorption ability. CONCLUSIONS: Analysis of the adsorption mechanism indicated that the Alg‐Chi adsorbed Pb 2+ mainly through ion exchange and chemical coordination. Green and low‐cost raw materials, simple preparation process, efficient removal efficiency and recyclable, these characteristics give the synthetic Alg‐Chi broad application prospects in the field of Pb 2+ ‐containing wastewater treatment. © 2018 Society of Chemical Industry